2010
DOI: 10.1186/1471-2377-10-45
|View full text |Cite
|
Sign up to set email alerts
|

Visual field defects of optic neuritis in neuromyelitis optica compared with multiple sclerosis

Abstract: BackgroundNeuromyelitis optica (NMO) is an inflammatory demyelinating disease that predominantly affects the optic nerves and the spinal cord, and is possibly mediated by an immune mechanism distinct from that of multiple sclerosis (MS). Central scotoma is recognized as a characteristic visual field defect pattern of optic neuritis (ON), however, the differing pathogenic mechanisms of NMO and MS may result in different patterns of visual field defects for ON.MethodsMedical records of 15 patients with NMO and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 30 publications
(37 reference statements)
5
49
0
1
Order By: Relevance
“…The pattern of visual field abnormalities following ON might also be diagnostically relevant. This holds particularly true of altitudinal deficits, which were encountered in NMO (>10% patients), but not in MS 28 29. This type of visual field defect is typical of ischaemic ON and might suggest involvement of vascular mechanisms in the pathogenesis of NMO-associated ON 28 29…”
Section: Clinical Phenotypesmentioning
confidence: 97%
“…The pattern of visual field abnormalities following ON might also be diagnostically relevant. This holds particularly true of altitudinal deficits, which were encountered in NMO (>10% patients), but not in MS 28 29. This type of visual field defect is typical of ischaemic ON and might suggest involvement of vascular mechanisms in the pathogenesis of NMO-associated ON 28 29…”
Section: Clinical Phenotypesmentioning
confidence: 97%
“…18 There was a significant reduction of GCL/IPL thickness in both hemifields of ON eye (28.5% and 30.5% reduction, P ϭ 0.0001 and P Ͻ 0.0001 for inferior and superior retina, respectively) ( Table 2). Reduction was significant at all eccentricities for both affected hemifields (P Ͻ 0.02 for all points) (Fig.…”
Section: Multiple Sclerosis Groupmentioning
confidence: 99%
“…On the other hand, in a study by Nakajiuma et al, altitudinal visual defect was also shown to be the most frequent non-central scotom pattern in NMO patients. Based on their results, they suggested possible NMO-IgG mediated ischemic injury as an explanation of ON development in NMO patients [2]. At this point, we would like to state that cranial MRI findings of our patient may add substantial perspectives to these arguments.…”
Section: Case Reportmentioning
confidence: 96%
“…Recently, other disorders such as neuromyelitis optica (NMO) has also been suggested to cause optic neuritis (ON) presenting with altitudinal field defect [2]. Herein, we illustrate clinical and neuroimaging findings of a patient presenting with ON in the form of altitudinal visual field defect who finally received the diagnosis of NMO.…”
Section: Introductionmentioning
confidence: 97%